First report of Xanthomonas oryzae pv. oryzicola causing bacterial leaf streak of rice in Burundi - Afolabi, O.; Milan, B.; Amoussa, R.; Koebnik, R.; Poulin, L.; Szurek, B.; Habarugira, G.; Bigirimana, J.; Silué, D. (Scientific Societies, 2014)
On May 9, 2013, symptoms reminiscent of bacterial leaf streak (BLS) caused by Xanthomonas oryzae pv. oryzicola were observed on rice plants at the panicle emergence stage at Musenyi, Gihanga, and Rugombo fields in Burundi. Affected leaves showed water-soaked translucent lesions and yellow-brown to black streaks, sometimes with visible exudates on leaf surfaces. Symptomatic leaves were ground in sterile water and the suspensions obtained were subjected to a multiplex PCR assay diagnostic for X. oryzae pathovars (3). Three DNA fragments (331, 691, and 945 bp) corresponding to X. oryzae pv. oryzicola were observed after agarose gel electrophoresis. Single bacterial colonies were then isolated from surface-sterilized, infected leaves after grinding in sterile water and plating of 10-fold dilutions of the cell suspension on semi-selective PSA medium (4). After incubation at 28°C for 5 days, each of four independent cultures yielded single yellow, mucoid Xanthomonas-like colonies (named Bur_1, Bur_2, Bur_6, and Bur_7) that resembled the positive control strain MAI10 (1). These strains originated from Musenyi (Bur_1), Gihanga (Bur_2), and Rugumbo (Bur_6 and Bur_7). Multiplex PCR assays on the four putative X. oryzae pv. oryzicola strains yielded the three diagnostic DNA fragments mentioned above. All strains were further analyzed by sequence analysis of portions of the gyrB gene using the universal primers gyrB1-F and gyrB1-R for PCR amplification (5). The 762-bp DNA fragment was identical to gyrB sequences from the Asian X. oryzae pv. oryzicola strains BLS256 (Philippines), ICMP 12013 (China), LMG 797 and NCPPB 2921 (both Malaysia), and from the African strain MAI3 (Mali) (2). The partial nucleotide sequence of the gyrB gene of Bur_1 was submitted to GenBank (Accession No. KJ801400). Pathogenicity tests were performed on greenhouse-grown 4-week-old rice plants of the cvs. Nipponbare, Azucena, IRBB 1, IRBB 2, IRBB 3, IRBB 7, FKR 14, PNA64F4-56, TCS 10, Gigante, and Adny 11. Bacterial cultures were grown overnight in PSA medium and re-suspended in sterile water (1 × 108 CFU/ml). Plants were inoculated with bacterial suspensions either by spraying or by leaf infiltration (1). For spray inoculation, four plants per accession and strain were used while three leaves per plant and four plants per accession and strain were inoculated by tissue infiltration. After 15 days of incubation in a BSL-3 containment facility (27 ± 1°C with a 12-h photoperiod), the spray-inoculated plants showed water-soaked lesions with yellow exudates identical to those seen in the field. For syringe-infiltrated leaves, the same symptoms were observed at the infiltrated leaf area. Re-isolation of bacteria from symptomatic leaves yielded colonies with the typical Xanthomonas morphology that were confirmed by multiplex PCR to be X. oryzae pv. oryzicola, thus fulfilling Koch's postulates. Bur_1 has been deposited in the Collection Française de Bactéries Phytopathogènes as strain CFBP 8170 ( http://www.angers-nantes.inra.fr/cfbp/ ). To our knowledge, this is the first report of X. oryzae pv. oryzicola causing bacterial leaf streak on rice in Burundi. Further surveys will help to assess its importance in the country.References: (1) C. Gonzalez et al., Mol. Plant Microbe Interact. 20:534, 2007. (2) A. Hajri et al. Mol. Plant Pathol. 13:288, 2012. (3) J. M. Lang et al. Plant Dis. 94:311, 2010. (4) L. Poulin et al. Plant Dis. 98:1423, 2014. (5) J. M. Young et al. Syst. Appl. Microbiol. 31:366, 2008.